2015
DOI: 10.1108/ilt-02-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Tightness testing of rotary ferromagnetic fluid seal working in water environment

Abstract: 2015),"Surface and wear mechanisms analysis of phosphorous-free and conventional engine lubricants on cylinder liner and piston rings surfaces", Industrial Lubrication and Tribology, Vol. 67 Iss 5 pp. 441-448 http://dx.(2015),"A new logarithmic profile model and optimization design of cylindrical roller bearing", Industrial Lubrication and Tribology, Vol. 67 Iss 5 pp. 498-508 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Van der Wal et al reported that when the sealing and magnetic liquid interfaces are unstable, the liquids emulsify, leading to seal failure [7]. Szczech and Horak noted that different speeds of two liquids cause Kelvin-Helmholtz (KH) instability at the two-phase interface, which also caused seal failure [9]. Qian proposed an approximate treatment method for liquid interface stability analysis and reported that interface instability is the main cause of seal failure [10].…”
Section: Introductionmentioning
confidence: 99%
“…Van der Wal et al reported that when the sealing and magnetic liquid interfaces are unstable, the liquids emulsify, leading to seal failure [7]. Szczech and Horak noted that different speeds of two liquids cause Kelvin-Helmholtz (KH) instability at the two-phase interface, which also caused seal failure [9]. Qian proposed an approximate treatment method for liquid interface stability analysis and reported that interface instability is the main cause of seal failure [10].…”
Section: Introductionmentioning
confidence: 99%
“…reported that when sealing and magnetic liquid interfaces are unstable, the liquids emulsify, leading to seal failure [7] . Szczech and Horak noted that speed differences between the two liquids caused Kelvin-CHINESE JOURNAL OF MECHANICAL ENGINEERING •4• Helmholtz (KH) instability at the two-phase interface, which also led to seal failure [9] . Qian proposed an approximate treatment method for liquid interface stability analysis and reported that interface instability is the main cause of seal failure [10] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to ordinary sealing, magnetofluid sealing has many strength points such as no wear, no leakage, no contamination, and lasting service life [2]. erefore, magnetofluid seals are widely used in dynamic seals, isolation seal, and environmental seal [3][4][5].…”
Section: Introductionmentioning
confidence: 99%